Mastering Macromedia Director 5 - Henderson, Chuck (San Francisco, Calif. : SYBEX, 1997)
Masters the latest Xtras and XObjects, featuring Xtras/XObjects, vid eo tutorials, and evaluation copies of 10 Macromedia products, includin g Director.
Includes index.
Version 5 for Windows and Macintosh.
"For Windows and Mac"--Cover.
"1834-8"--Spine.
Keywords: Director (Computer file); Multimedia systems; Computer graphics; Interactive multimedia